Assessing Obsolescence of Software Engineers - Santos, Alessandro; Rocha, Bruno; França, César (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
Unlike other professions, where knowledge and skills become obsolete more slowly, it is estimated that an IT professional will become obsolete in two years. Thus, the accurate assessment of technical skills can help software engineers to take the necessary actions to mitigate the risk of professional obsolescence. This work proposes a method to assess the degree of professional obsolescence, based on the concept of Participatory Sensing Network. To evaluate the proposed method, we collected data from 50 software engineers, and presented it to 9 professional recruiters to reach a measure of their actual employability. Then, we compared these data against the calculations of our algorithm. The results showed no significant difference between the traditional recruitment process and the proposed algorithm, which means that the algorithm can be an accurate surrogate for such employability assessment.